2014
DOI: 10.1152/ajplung.00156.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pim1 kinase protects airway epithelial cells from cigarette smoke-induced damage and airway inflammation

Abstract: Exposure to cigarette smoke (CS) is the main risk factor for developing chronic obstructive pulmonary disease and can induce airway epithelial cell damage, innate immune responses, and airway inflammation. We hypothesized that cell survival factors might decrease the sensitivity of airway epithelial cells to CS-induced damage, thereby protecting the airways against inflammation upon CS exposure. Here, we tested whether Pim survival kinases could protect from CS-induced inflammation. We determined expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In childhood asthma, exacerbations due to HRV-C have been associated with more severe exacerbations than other HRV groups [7,8]. In stable children with CF the presence of HRV-C or HRV-A2 is associated with an increased frequency of exacerbations [9].…”
Section: Pathogenicity Of Individual Rhinovirus Species During Exacermentioning
confidence: 99%
See 1 more Smart Citation
“…In childhood asthma, exacerbations due to HRV-C have been associated with more severe exacerbations than other HRV groups [7,8]. In stable children with CF the presence of HRV-C or HRV-A2 is associated with an increased frequency of exacerbations [9].…”
Section: Pathogenicity Of Individual Rhinovirus Species During Exacermentioning
confidence: 99%
“…Pim1 kinase is a constitutively active serine/threonine kinase known to be involved in cell survival by increasing the threshold for apoptosis [6,7]. We have shown previously that Pim1 kinase is highly expressed in the bronchial airway epithelium and that pharmacological inhibition of Pim1 kinase increases the sensitivity of bronchial epithelial cells to cell death upon challenge with cigarette smoke extract [8]. Therefore, we hypothesised that inhibition of Pim1 kinase activity in virally infected PBECs would enhance the onset of cell death, resulting in reduced viral replication.…”
mentioning
confidence: 99%
“…CS exposure has been shown to induce an abnormal inflammatory response in the small airways and alveoli, contributing to airway remodeling and subsequent reduction of the airflow, which is the main characteristic of COPD1. It has been demonstrated that bronchial epithelium acts as a main source of overproduction of various cytokines, chemokines and adhesion molecules that modulate other elements of the airway wall and immune cells against CS23. Therefore, mapping the molecular mechanisms for CS-induced alterations in bronchial epithelial cells may offer clues into COPD pathogenesis and treatment.…”
mentioning
confidence: 99%
“…As a consequence of the inflammation microenvironment and massive cell death induced by HPV or smoking, chronic inflammation occurs [14,26,28,29] . Increasing inflammation-related proteins, CRP and cytokines, and TNFα in the plasma of H&N cancer patients supported our assumption [12] .…”
Section: Discussionmentioning
confidence: 99%